Anxiety, depression & anger toolbox for teens : 50 powerful mindfulness, CBT and positive psychology activities to manage your emotions - Bernstein, Jeffrey, 1961- (PESI Publishing & Media, 2020)
This new mood management toolbox brings together the powers of mindfulness, CBT and positive psychology for teens to take control of their distressing thoughts and over-the-top emotions.